IMPORTANCE AND PERFORMANCE ANALYSIS OF COMPENSATION IN PT. BANK CENTRAL ASIA TBK. KCU MANADO - William, Reo Jubert; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Bank is a financial institution that generally built with an authority to receive money loan, and lend money to the client. Human resource management is one of management field that is specially learn about people’s connection and role in organization. The employee performance is firmly connected with the salary and incentive that they receive because it will be a positive nor negative impact to the quality of working and eventually will raise employee’s performance in an organization. Employee performance optimization as proof from the company side to raise their profit. The aim of this study is to analyze the importance and performance of compensation criteria such as salary, health insurance, bonuses, employee benefit, and overtime. This research is casual type of research, which uses primary data obtained through questionnaires and uses importance and Performance Analysis. 100 respondents are the sample size of this research. The result of this study shows that salary placed in quadrant I (very important but low performance), health insurance, bonuses, and employee benefit placed in quadrant II (very important and high performance), while overtime placed in quadrant III (low importance and low performance). So, related with the findings in this research, there are some recommendations for PT. Bank Central Asia TBK. KCU Manado.Keywords: Banking, Compensation, Salary, Health Insurance, Bonuses, Employee Benefit, Overtime, Importance and Performance Analysis.